Interpersonal expectations (Theory, research, and applications) (Cambridge, New York, 1993)
This book examines the phenomenon of interpersonal expectations form theoretical, applied, and basic research perspectives. The book is divided into three parts that review real-world applications, such as the courtroom, the classroom, and the operating room; the meditation of interpersonal expectations through verbal and nonverbal behavior; and the emerging methodological and statistical techniques for understanding the implications of interpersonal expectations. In each part, critical commentary and analysis by leading scholars in the field are presented
Keywords: expectation ( psychology ),interpersonal relations